The Strategy to Optimize the Role of Government Internal Supervisory Apparatus (APIP) in Procurement Fraud Risk Management in Industry 4.0 - Kamal, Mustofa; Elim, John (Jurnal Tata Kelola dan Akuntabilitas Keuangan Negara, 2021)
Many challenges confront the efforts to build procurement fraud risk management in Industry 4.0. This study aims to assess the risk of procurement fraud in industry 4.0 and disclose strategies to optimize the role of internal auditors in mitigating these risks. The mixed-method has been conducted with data on procurement fraud risks generally accepted by government agencies. A survey involving 140 respondents and interviews with five experts have been completed. The risk assessment in the research findings involved seven procurement fraud risks, with "collusion between providers in e-tendering" ranking the highest. Procurement management must detect and prevent fraud by creating anti-hacker applications, conducting data analytics on business ownership, and ongoing monitoring. Internal auditors must undertake fraud prevention by improving their ability in data analytics, encouraging probity plans, and procurement assistance. Fraud detection is carried out through performance audits using computer-assisted audit techniques, probity audits, information technology governance audits, continuous audits, data analytics, and internal auditor integrity assessments through surveys to the auditee.